Implementasi Marketing 4.0 Melalui Program Isp (Interactive Session Program) Dalam Meningkatkan Kepuasan Orang Tua Di Global Islamic Boarding School (GIBS) - Khairun Nikmah; Khuzaini; Zakky Zambrudi; Syahrial Shaddiq (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the implementation of the Marketing 4.0 strategy at Global Islamic Boarding School (GIBS) through the Interactive Session Program (ISP), facilitated by the Parent Communication and Engagement Department. The research approach used descriptive qualitative methods with observation and survey techniques. The study subjects included 347 employees and 337 parents. Observations showed that 80% of parents were satisfied with the ISP program because it provided direct access to information about their children's progress at school and in the boarding school. The findings indicate that the Marketing 4.0 strategy at GIBS is not only digitally based through social media, but also relationally based through intensive communication between the school and parents. The ISP program has been proven to strengthen emotional bonds, increase parent satisfaction, and be an effective marketing strategy in building the institution's image.